Investigation of environmentally friendly power generation systems for low-grade waste heat recovery - Albatati, Faisal Ali S. (2015)
From the point of view of energy importance and the environmental impacts associated with conventional energy production methods, and for the purpose of low-grade waste heat recovery, this thesis demonstrates an investigative approach to develop and test a novel, environmentally friendly small-scale Rankine based power generation prototype system. To fulfil the aim, a range of systems of different technologies, and employing different working fluids were investigated to identify the most efficient, cost-effective system for the application. These systems are the absorption power generation system, and the flood expansion power generation system employing CO2/Lubricant mixture as the working fluid, the CO2 SRC power system, and finally the ORC system employing newly developed HFOs and HCFOR1233zd(E) refrigerants. The CO2/lubricant working fluid mixture was experimentally investigated and thermodynamically modelled. The performance of the investigated systems was theoretically evaluated by computer simulations. The results revealed that the ORC outperformed all other investigated systems, achieving thermal efficiency and net thermal power output of 14.36% and 4.81 kW respectively with R1233zd(E). In addition, the evaluation confirmed the capability of the new refrigerants to replace conventional refrigerants. A small-scale R1233zd(E) ORC prototype system utilising a specially developed scroll expander was constructed and tested. In the First Experiment, an automotive motor was utilised as the electric generator. The system’s optimum performance was 7.87% thermal efficiency, 1.39 kW expander power output, and 180 W electric power output. The main source of performance limitation was identified as the lower capability of the steam humidifier heat source, in addition to the speed mismatch between the expander and the motor, the poor performance of the circulation pump, and the piping configuration in relation to the positions of heat exchangers. Piping and the position of heat exchangers were altered, the motor was replaced by an alternator and the second experiment commenced in which the best overall experimental performance of 7.6% thermal efficiency, 1 kW expander power output, 246 W electric power output, was achieved. Very poor pump efficiency and a large power loss through the power transmission mechanism to the alternator were observed. Upon completion of the experiments, the theoretically predicted performance was validated, and the experimentally obtained results were compared to those of similar ORCs from literature. The comparison revealed that for the utilised expander type, a mass flow rate of 0.074 kg/s, and a pressure ratio of 4.5, achieves the best expander efficiency of 75%. From an economic point of view, the R1233zd(E) ORC was shown to be a very attractive and safe investment even for scaled- up systems. The thesis concluded that the ORC technology remains the most efficient, flexible technology for low-grade heat recovery, and the evaluation of R1233zd(E) for the first time expressed the attractive potentials of the refrigerant in ORC applications. Finally, justified recommendations were made to replace the heat source and refrigerant pump and to test other types of expander in order to improve the performance of the R1233zd(E) ORC prototype system.